Poverty and inequality in the non-income multidimensional space: A critical review in the Arab States - Abdel-Hameed Nawar (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
This paper examines the substantive pros and cons of the multidimensional poverty index (MPI) recently developed by Oxford University's Poverty and Human Development Initiative (OPHI). It provides comparative cross-country and country-specific discussion on multidimensional poverty and inequality in the non-income space, with a special reference to the countries in the Arab region. Despite the large degree of subjectivity in selecting the dimensions and the cut-off threshold (k=3) determining the minimum number of dimensions required to identify whether or not a household is multidimensionally poor, the MPI has an important advantage of capturing more dimensions of human deprivations and includes both the level of human deprivation and a measure of the intensity of poverty using micro survey data. Using survey data from 13 Arab countries with a combined population of 221.2 million in 2007, the OPHI estimated that 41.2 million people, representing 18.64 per cent of the combined population were living in multidimensional poverty in 2007, with an average intensity of 50.9. It is shown that the average intensity (A) has a strong positive correlation to headcount (H) in the Arab region. Somalia has the highest MPI value, 81 per cent of the population, with deprivation concentrated in indicators of living standard. The United Arab Emirates, the only Gulf Cooperation Council (GCC) state considered here, has the lowest MPI value, 0.57, with deprivation concentrated in education. Arab Mashreq countries have highest deprivation in both education and health, while Arab Maghreb countries have low deprivation in health and education but also in standard of living compared to both Arab Least Developed Countries (LDCs) and Arab Mashreq countries.
Keywords: 330; Einkommensverteilung; Armut; Disparitätsmaß; Arabische Staaten